Callitriche antarctica Engelm. ex Hegelmaier 1867 - Lansdown, Richard V. (Zenodo, 2022)
1. Callitriche antarctica Engelm. ex Hegelmaier (1867: 20) Type: — FRANCE. ÎLES KERGUELEN: 1839–1843, J.D. Hooker s.n. (lectotype [designated by Lansdown and Hassemer 2021: 88] MEL 2409648! [Figure 2]; isolectotype W 0122126!). Epitype (designated Lansdown and Hassemer 2021: 88): FRANCE. ÎLES KERGUELEN: Grande Terre, Port-aux-Français, elephant seal wallows next to greenhouses, 5 m, 30 December 2011, R.C. Winkworth & F. Hennion 42 (P 02432590! [Figure 3]). Description (from Lansdown and Hassemer 2021):—Stem and leaf scales present, at least in some populations. Leaf bases broadly connate, forming a cup. Lower leaves reduced to scarious, spathulate, evanescent scales. Lingulate leaves unknown; expanded submerged or floating leaves somewhat fleshy, 2.3–10.0(–18.0) mm long × 1.3–4.8 mm wide, irregularly 3-veined and sometimes additional free veins from the midrib and side nerves, apical leaves may form a floating rosette; terrestrial leaves somewhat fleshy, similar to expanded leaves but generally smaller. Flowers solitary; upper flowers ♂, lower ♀. Bracts lacking. Styles erect, persistent, 1.4–3.2 mm long. Filament short and stout before dehiscence, lengthening to 14 mm long and becoming more delicate after dehiscence; anthers 0.6–0.7 mm long × 0.7–0.8 mm wide, quadrilocular; pollen yellow. Fruit not strumose, subsessile, as wide as or wider than high, dull brown or blackish when mature, 0.7–1.3 mm long × 0.7–1.5 mm wide, unwinged. Illustrations: —Plates 1169(11) and 1171(9) in Fassett (1951); Figures 6 (a–b) and 6A(a–e) in Mason (1959); Figure 6 in Bacigalupo (1979); Figure 1 (b) in Lansdown and Hassemer 2021. Fig. 1a. Recognition: — C. antarctica can be distinguished from all other Callitriche species except C. aucklandica by the fleshy leaves with connate bases. C. aucklandica differs from C. antarctica in the narrow wing on the fruit, however this can be difficult to discern, particularly on herbarium specimens, which is why doubt remains as to the occurrence of C. antarctica on the Auckland Islands. ...